2020
DOI: 10.21203/rs.3.rs-90362/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

METTL3-Mediated m6A mRNA Modification of FBXW7 Suppresses Lung Adenocarcinoma

Abstract: BackgroundFBXW7 m6A modification plays an important role in lung adenocarcinoma (LUAD) progression; however, the underlying mechanisms remain unclear.MethodsThe correlation between FBXW7 and various genes related to m6A modification was analyzed using The Cancer Genome Atlas database. The regulatory effects of METTL3 on FBXW7 mRNA m6A modification were examined in a cell model, and the underlying mechanism was determined by methylated RNA immunoprecipitation, RNA immunoprecipitation, luciferase reporter, and m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Evidently, m 6 A RNA methylation is a major inactivation mechanism of tumour suppressor genes in tumorigenesis 27–29 . In order to investigate the roles of the m 6 A methylation modification‐associated genes in the progression of RCC, we used MeRIP‐seq to analyse the difference of the m 6 A methylation level in the five paired RCC tissues and adjacent normal tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, m 6 A RNA methylation is a major inactivation mechanism of tumour suppressor genes in tumorigenesis 27–29 . In order to investigate the roles of the m 6 A methylation modification‐associated genes in the progression of RCC, we used MeRIP‐seq to analyse the difference of the m 6 A methylation level in the five paired RCC tissues and adjacent normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, m 6 A RNA methylation is a major inactivation mechanism of tumour suppressor genes in tumorigenesis. [27][28][29] In order to investigate the roles of the m 6 A methylation modification-associated genes in the progression of RCC, we used MeRIP-seq to analyse the difference of the m 6 A methylation level in the five paired RCC tissues and adjacent normal tissues. MeRIP-seq analysis revealed that there were 369 hypermethylated and upregulated (hyper-up) genes, 374 hypomethylated and downregulated (hypo-down) genes, 14 hypermethylated and downregulated (hyper-down) genes and two hypomethylated and upregulated (hypo-up) genes in RCC tissues compared to adjacent normal tissues (Figure 1H and Table S4).…”
Section: Downregulation Of Znf677 Is Associated With Unfavourable Pro...mentioning
confidence: 99%
“…METTL3 consumption signi cantly suppressed tumorigenicity and metastasis, but in patients with hepatocellular carcinoma, METTL3 was signi cantly upregulated, and the OS rate was shortened [18]. METTL3 expression was elevated in pulmonary adenocarcinoma, and METTL3 promoted the growth, survival, and invasion of human pulmonary carcinoma cells [19]. Lin et al reported that METTL3 could promote cellular growth, survival, and invasion by increasing the expression of EGFR and TAZ [20], revealing the signi cant function of METTL3 in boosting the translation of oncogenes in human pulmonary carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A previous research conducted by our team revealed that N6methyladenosine (m 6 A) is involved in the methylated modification of FBW7 mRNA (52). M 6 A refers to the methylation of N6-adenosine in eukaryotic mRNA controlled by writers-methyltransferases, erasers-demethylases, and readers-binding proteins, which is a universal modification of mRNA and affects various pathphysiological processes including tumorgensis (53,54).…”
Section: Rna Epitranscriptomic Modification Of Fbxw7mentioning
confidence: 99%